Application of an integrated device for ultra-low temperature desulfurization and denitration in large rotary kiln - Zheng, Tao; Tao, Ying; Luo, Xudong; Qi, Xin; Zhao, Jingming; Wang, Xingbu; Fei, Xiangtong; Wang, Lianyong (Transactions on Engineering and Technology Research, 2024)
To tackle the problem of excessive nitrogen oxide emissions during the denitration process of the lime rotary kiln at Beitai Iron Mine, it was proposed to integrate ultra-low temperature SCR denitration catalysts and a moving-burden bed reactor into a radial combined desulfurization and denitration device to achieve ultra-low temperature denitration in a low-sulfur state. The self-built integrated device features two desulphurization beds and one denitration bed, through which the flue gas passes successively in a radial flow manner. Industrial test results indicate that the denitration efficiency reached an average of 96.07% at temperatures ranging from 70 to 130°C during a 14-day test period, indicating a good denitration effect. The ultra-low temperature SCR denitration device has been put into use, effectively reducing nitrogen oxide emissions and air pollution, while also promoting the optimization and upgrading of the energy structure. The research results can provide a reference for the environmental management of mining and processing enterprises.